Suicidal risk and psychopathological profiles in adolescents with neurodevelopmental disorders: an Italian multicentric study - Cardillo, Ramona; Di Modica, Irene; Cucinotta, Francesca; Galletta, Federica; Raffagnato, Alessia; Di Cara, Marcella; De Domenico, Carmela; Germanò, Eva; Carucci, Sara; Abbracciavento, Giuseppe; Murtas, Rita; Donia, Alessia; et al. (Frontiers in Psychiatry, 2025)
IntroductionSuicidal spectrum behaviors (SSB) consist of a continuum ranging from non suicidal self-injury, suicidal ideation, and suicide attempt to committed suicide. In adolescence, suicide is currently the second cause of death among adolescents aged 15 to 24 years and the third leading cause in children aged 10 to 14 years. Adolescents with Neurodevelopmental Disorders (NDDs), especially those with Autism Spectrum Disorder and Attention Deficit/Hyperactivity Disorder, are at heightened risk.MethodsThis is a cross-sectional, multicenter research study, which involves four Italian child neuropsychiatry units (Messina, Padua, Rimini, and Cagliari). The study aims to define a specific neuropsychological and psychopathological profile associated with suicidal behaviors in adolescents and pre-adolescents with NDDs (11–18 years). In a sample of 127 NDDs adolescents (60 females and 67 males), with and without SSB, several variables were compared through standardized measures, including emotional dysregulation, impulsivity, and irritability as well as environmental risk factors.ResultsThe results of this study are consistent with the literature data and suggest that emotional dysregulation (p <.001) as an individual factor and Adverse Childhood Experiences (p = .002), as environmental factors, play a key role in promoting suicidality in pre-adolescents and adolescents with NDDs.DiscussionThis awareness prompts the implementation of useful prevention methods during the clinical follow-up of individuals with NDDs.